Improving index-based drought insurance in varying topography: evaluating basis risk based on perceptions of Nicaraguan hillside farmers - Kost, André; Läderach, Peter R.D.; Myles, Fisher; Cook, Simon E.; Gómez, Lorena (Public Library of Science, 2012)
This paper discusses a methodology to model precipitation indices and premium prices for index-based drought insurance for smallholders. Spatial basis risk, which is borne by the insured, is a problem, especially in variable topography. Also, site-specific drought risk needs to be estimated accurately in order to offer effective insurance cover and ensure financial sustainability of the insurance scheme. We explore farmers' perceptions on drought and spatial climate variability and draw conclusions concerning basis risk with regards to the proposed methodology. There are technically many options to represent natural heterogeneity in index insurance contracts while serving the customer adequately and keeping transaction costs low.